Прогнозирование показателей рынка труда строительной сферы - Залунина, О. М.; Дружинина, В. В. (Ways to Improve Construction Efficiency, 2012)
In the article the algorithm of the method of harmonic balance with respect to forecasting performance of the labor market in construction.